Ensuring Educational Escape-Room Success: The Process of Designing, Piloting, Evaluating, Redesigning, and Re-Evaluating Educational Escape Rooms. (February 2021) - Eukel, Heidi; Morrell, Briyana
Background: The implementation of educational escape rooms has shown great value in learner outcomes. The design of such simulations requires a thoughtful, well-defined process. Objective: The purpose of this article is to encourage educational escape room designers to use a thoughtful, methodical, iterative process to ensure quality, educational capacity, and a positive learner experience. Application: When designing an educational escape room, designers should consider implementing a cyclic design process: design, pilot, evaluate, redesign, re-evaluate, and repeat. Discussion: A methodological process for educational escape room design can promote deep learning and positive student perceptions.